Reasons for Energy Drink Use and Reported Adverse Effects Among Adolescent Emergency Department Patients. Issue 12 (December 2017) - Nordt, Sean Patrick; Claudius, Ilene; Rangan, Cyrus; Armijo, Erick; Milano, Peter; Yanger, Sheryl; Tomaszsewski, Christian
Abstract : Objectives: There is concern of energy drink use by adolescents. The objective of this study was to evaluate the energy drink consumption use, frequency, age of first use, reasons for use, influences of choice of brand, and adverse events recorded in a predominant Latino adolescent population. Methods: Subjects between the ages of 13 and 19 years utilizing emergency department services for any reason at a large county hospital answered a questionnaire about energy drink usage. Results: There were 192 subjects, of which 49% were male and 51% were female. Latino adolescents were 85% of the participants, although other ethnic groups participated including African American, white, and Asian. Reasons for use include 61% to increase energy, 32% as study aide, 29% to improve sports performance, and 9% to lose weight. Twenty-four percent reported using energy drinks with ethanol or illicit drugs including marijuana, cocaine, and methamphetamine. Adverse reactions were reported in 40% of the subjects including insomnia (19%), feeling "jittery" (19%), palpitations (16%), gastrointestinal upset (11%), headache (8%), chest pain (5%), shortness of breath (4%), and seizures (1%). Conclusions: Both brand name and packaging influenced the choice of energy drink in most subjects. Forty percent reported at least 1 adverse effect. While most adverse effects were not severe, a small number are serious. In addition, we showed intentional ingestion with ethanol and illicit drugs. Of additional concern is that both brand and packaging seem to directly affect choice of energy drink consumed.